Pemikiran Modern dalam Islam (Islam Integratif, Interkonektif) Menurut Pemikiran Amin Abdullah - M. Anang Sholikhudin; Nabilah Maulidah Aliyyah; M. Khusni Mubarok (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the modern Islamic thought developed by Amin Abdullah, particularly through the concept of integrative and interconnective Islam. The main issue discussed is the fragmentation between religious sciences (naqliyah) and modern sciences (‘aqliyah) in the contemporary Islamic knowledge corpus. The purpose of this research is to analyze Amin Abdullah’s efforts in reconstructing the epistemology of Islamic knowledge through the integration of these two domains of knowledge. This research uses a qualitative-descriptive approach with a literature study method, analyzing Amin Abdullah's key works and relevant academic discourses. The results show that the integrative-interconnective paradigm offered by Amin Abdullah provides a holistic framework for understanding Islam in the modern era. This approach encourages a dialogical relationship between religion, science, and social reality, ensuring that Islamic thought remains relevant and dynamic amidst global changes. The study concludes that Amin Abdullah's perspective makes a significant contribution to the renewal of Islamic scholarship by bridging tradition and modernity. Thus, this integrative-interconnective perspective is expected to enrich the development of Islamic thought in a more inclusive and open manner.